The Regional Värmland SOM Survey 2010 - SOM Institute, University of Gothenburg (University of Gothenburg, 2012)
This is the first SOM survey carried out in the county of Värmland. The questionnaire consists of nine coherent parts: news and media; politics, society and democracy; regionalization and regional development; society and service; culture, identity and life style; globalization; working life; the election 2010; and background

Purpose:

Study attitudes and behaviours that are linked to local and regional issues and phenomena

Detta är den första SOM-undersökning som genomförts i Värmland. Frågeformuläret består av nio sammanhållna frågeområden: nyheter och media; politik, samhälle och demokrati; regionalisering och regional utveckling; samhälle och service; kultur, identitet och livsstil; globalisering; arbetsliv; valet 2010; samt bakgrundsfrågor.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
SOM-undersökningen i Värmland 2010
Värmlands-SOM 2010
Keywords: internal politics; inrikespolitik; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap